Becoming Asian American : second-generation Chinese and Korean American identities - Kibria, Nazli (Johns Hopkins University Press, 2002)
In Becoming Asian American, Nazli Kibria draws upon extensive interviews she conducted with second-generation Chinese and Korean Americans in Boston and Los Angeles who came of age during the 1980s and 1990s to explore the dynamics of race, identity, and adaptation within these communities. Moving beyond the frameworks created to study other racial minorities and ethnic whites, she examines the various strategies used by members of this group to define themselves as both Asian and American. In her discussions on such topics as childhood, interaction with non-Asian Americans, college, work, and the problems of intermarriage and child-raising, Kibria finds wide discrepancies between the experiences of Asian Americans and those described in studies of other ethnic groups. While these differences help to explain the unusually successful degree of social integration and acceptance into mainstream American society enjoyed by this "model minority," it is an achievement that Kibria's interviewees admit they can never take for granted. Instead, they report that maintaining this acceptance "requires constant effort on their part." Kibria suggests further developments may resolve this situation - especially the emergence of a new kind of pan-Asian American identity that would complement the Chinese or Korean American identity rather than replace it